Oral health studies in the 1982 Pelotas (Brazil) birth cohort: methodology and principal results at 15 and 24 years of age Estudo longitudinal de saúde bucal na coorte de nascidos vivos em Pelotas, Rio Grande do Sul, Brasil, 1982: aspectos metodológicos e resultados principais aos 15 e 24 anos de idade - Karen Glazer Peres; Marco Aurélio Peres; Flavio Fernando Demarco; Sandra Beatriz Chaves Tarquínio; Bernardo L. Horta; Denise P. Gigante (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to describe the methodology and results of oral health studies nested in a birth cohort in Pelotas, Southern Brazil. For the oral health studies a sub-sample (n = 900) was selected from the cohort and dental examinations and interviews were performed at ages 15 (n = 888) and 24 years (n = 720; 81.1%). Data collection included dental outcomes, dental care, oral health behaviors, and use of dental services. Mean DMF-T varied from 5.1 (SD = 3.8) to 5.6 (SD = 4.1) in the study period. The proportion of individuals with at least one filled tooth increased from 51.9% to more than 70%. Individuals who had always been poor used dental services less and had fewer healthy teeth on average than those who had never been poor. Individuals with decreasing or increasing family income trajectories showed intermediate values. An increase was seen in the number of healthy teeth from age 15 to 24 only among those who had never been poor. A history of at least one experience with poverty had a negative impact on oral health in adulthood. Descreveu-se a metodologia e os resultados dos estudos de saúde bucal em uma coorte de nascimentos. Em 1997, uma amostra da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, (n = 900) foi sorteada para o estudo de saúde bucal (15 anos) e os mesmos indivíduos foram novamente investigados aos 24 anos. Agravos bucais, cuidados com a saúde bucal e uso de serviços odontológicos foram avaliados. Participaram do estudo 888 adolescentes aos 15 anos e 720 (81,1%) aos 24. O índice CPO-D médio variou de 5,1 (DP = 3,8) a 5,6 (DP = 4,1) no período. Ter pelo menos um dente restaurado passou de 51,9% aos 15 anos para mais de 70% aos 24. A proporção do uso de serviços e a média de dentes saudáveis foram menores dentre os sempre pobres quando comparados àqueles nunca pobres. Indivíduos com trajetórias econômicas descendente ou ascendente tiveram valores intermediários. Aumento de dentes saudáveis dos 15 aos 24 anos foi observado apenas dentre aqueles nunca pobres. Apresentar pelo menos um episódio de pobreza ao longo da vida impactou na saúde bucal na vida adulta.